István Rév - The History of the CEU
Interview with István Rév Professor at CEU and the Director of OSA Archivum where he talks about his early connections with CEU and how the idea of such a university in Budapest was born. He explains why CEU was needed in Budapest, what were the reasons for creating an international University in the region, and why expanding the Dubrovnik courses would not have been sufficient in the context of post-communist states that were undergoing major historical changes in the beginning of the 90s. Contains an extensive discussion on the international character of the university in relation to the need of focusing on Central and Eastern European regions.